Mont-Saint-Michel and Chartres - Adams, Henry, 1838-1918 (Salt Lake City, UT : Project Gutenberg, 2003)
"Mont-Saint-Michel and Chartres" by Henry Adams is a book privately published in 1904. This playful meditation on medieval culture frames itself as a tour through three centuries, guiding readers through the worldview of the Middle Ages. Adams explores the Mont Saint Michel Abbey, the epic poem "Le Chanson de Roland," and extensively analyzes Chartres Cathedral, examining how architecture, poetry, and philosophy expressed medieval devotion to the Virgin Mary. The final chapters turn to intellectual figures like Peter Abelard, Francis of Assisi, and Thomas Aquinas, drawing connections between spiritual and architectural grandeur. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Mont_Saint_Michel_and_Chartres
Release date is 2003-10-01
Steve Harris, Charles Franks and the Online Distributed Proofreading Team.
Keywords: Civilization, Medieval; Mont-Saint-Michel (Abbey : France); Cathédrale de Chartres